Hypertension Care Assessment: Unveiling Effect of Medication Adherence, Diet, and Lifestyle A-Cohort Investigation - K. Rama Krishna; Safeena Roohi; S. Anand; I.T.N. Shalini; Dr. G. Prem Kumar; Dr. Y. Gopi; Dr. N. V. Rama Rao; Rama Rao Nadendla (The Bioscan, 2025)
Hypertension is a major risk factor for cardiovascular diseases in developing countries. Hence, managing high blood pressure is crucial in reducing associated complications and improving the quality of life. Along with antihypertensive therapy non-pharmacological approaches like lifestyle changes and dietary restrictions help in controlling high blood pressure levels. Lifestyle changes involve physical activity, alcohol abstinence, and cessation of smoking whereas dietary restrictions include salt restriction, consumption of vegetables and fruits, and reduced dairy products. Strict adherence to both medication and nonpharmacological modifications will result in good high-blood pressure control and can prevent high BP-associated complications, thereby improving QoL in Hypertensive individuals. This cohort investigation aims to assess the potential impact of nonpharmacological management along with medication adherence in controlling blood pressure.